Sensitized genetic backgrounds reveal differential roles for EGF repeat xylosyltransferases in Drosophila Notch signaling. - Pandey, A.; Li-Kroeger, D.; Sethi, M.K.; Lee, T.V.; Buettner, F.F.; Bakker, H.; Jafar-Nejad, H. (Glycobiology, 2018)
In multicellular organisms, glycosylation regulates various developmental signaling pathways including the Notch pathway. One of the O-linked glycans added to epidermal growth factor-like (EGF) repeats in animal proteins including the Notch receptors is the xylose-xylose-glucose-O oligosaccharide. Drosophila glucoside xylosyltransferase (Gxylt) Shams negatively regulates Notch signaling in specific contexts. Since Shams adds the first xylose residue to O-glucose, its loss-of-function phenotype could be due to the loss of the first xylose, the second xylose or both. To examine the contribution of the second xylose residues to Drosophila Notch signaling, we have performed biochemical and genetic analysis on CG11388, which is the Drosophila homolog of human xyloside xylosyltransferase 1 (XXYLT1). Experiments in S2 cells indicated that similar to human XXYLT1, CG11388 can add the second xylose to xylose-glucose-O glycans. Flies lacking both copies of CG11388 (Xxylt) are viable and fertile and do not show gross phenotypes indicative of altered Notch signaling. However, genetic interaction experiments show that in sensitized genetic backgrounds with decreased or increased Notch pathway components, loss of Xxylt promotes Delta-mediated activation of Notch. Unexpectedly, we find that in such sensitized backgrounds, even loss of one copy of the fly Gxylt shams enhances Delta-mediated Notch activation. Taken together, these data indicate that while the first xylose plays a key role in tuning the Delta-mediated Notch signaling in Drosophila, the second xylose has a fine-tuning role only revealed in sensitized genetic backgrounds.